In vitro evaluation of bioagents for the management of basal stem rot disease of coconut - Greena, K. K.; Jayarajan, Keerthana; Hegde, Vinayaka; Lakpale, N.; Daliyamol; Prathibha, V. H. (Journal of Plantation Crops, 2025)
Basal stem rot caused by Ganoderma spp. is an important disease affecting coconut. Being a soil-borne pathogen, it can persist in coconut ecosystem for longer periods. Therefore, an eco-friendly remedy for the management of Ganoderma is essential. Following soil sample collection and isolation, the current study evaluated the efficacy of fluorescent Pseudomonas and Trichoderma spp. against basal stem rot pathogen Ganoderma gibbosum in vitro using dual culture assay. Among the 15 isolates of fluorescent Pseudomonas evaluated, the inhibition varied between 41% and 80 %. P. aeruginosa (isolate P13) exhibited maximum inhibition of 80.36%. All the isolates of Trichoderma showed greater antagonistic capacity with percentage inhibitions ranging from 71% to 87 %. T. harzianum isolate T20 exhibited a maximum inhibition of 87.92%.The present study identified several efficient antagonists of Ganoderma spp that could be further utilized for the management of the pathogen in field conditions.